1996
DOI: 10.1111/j.1532-950x.1996.tb01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesic and Cardiopulmonary Effects in Dogs of Oxymorphone Administered Epidurally and Intramuscularly, and Medetomidine Administered Epidurally: A Comparative Clinical Study

Abstract: Thirty dogs undergoing pelvic or hindlimb orthopedic surgery were each administered one of the following postoperative treatments: intramuscular oxymorphone 0.15 mg/kg (OIM) (n = 10); epidural oxymorphone 0.05 mg/kg, (OEP) (n = 10); or epidural medetomidine, 0.015 mg/kg (MEP) (n = 10). Heart rate (HR), respiratory rate (RR), and arterial blood pressure were measured before drug injection and 15, 30, 60, 90, 120, 180, 240, 300, 360, 420, and 480 minutes postinjection (PI). Arterial blood gas analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 27 publications
3
23
0
1
Order By: Relevance
“…Scales described in veterinary studies have been either verbal ordinal 3-to 5-point scales (with descriptors such as none, mild, moderate, severe), numerical (ordinal) rating scales (e.g., a 4-to 10-point scale), categorized numerical rating scales with ordinal ranking of individual behaviors within three to seven "categories" (e.g., 0-2 points assigned for various behaviors within each of several behavior categories such as vocalization, movement, respiratory pattern, and posture), or visual analog scales (VAS 1 ). Verbal, numerical, categorized numerical, VAS, or a combination of two or more of these scales have been used to evaluate behavior in dogs in at least six studies of OHE or castration (Firth and Haldane 1999;Lascelles et al 1997;Lemke et al 2002;Slingsby and Waterman-Pearson 2000;Slingsby et al 2001); in 13 studies of orthopedic surgery (Brodbelt et al 1997;Budsberg et al 2002;Conzemius et al 1997;Day et al 1995;Grisneaux et al 1999;Hendrix et al 1996;Lascelles et al 1994;Mbugua et al 1989;Nolan and Reid 1993;Pibarot et al 1997;Sammarco et al 1996;Taylor and Houlton 1984;Vesal et al 1996); one study of auricular surgery (Buback et al 1996); seven studies of canine thoracotomies (Conzemius et al 1994;Pascoe and Dyson 1993;Popilskis et al 1991;Stobie et al 1995;Thompson and Johnson 1991;Vainio and Ojala 1994;Walsh et al 1999); and five studies of other soft tissue and/or orthopedic surgery patients ( Holton et al 1998a,b;Mathews et al 1996Mathews et al , 2001Reid and Nolan 1991). All of these scales are characterized by reliance on subjective evaluation of behaviors whose correlation with other behavioral or physiological indic...…”
Section: Potential Advantages For Investigatorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Scales described in veterinary studies have been either verbal ordinal 3-to 5-point scales (with descriptors such as none, mild, moderate, severe), numerical (ordinal) rating scales (e.g., a 4-to 10-point scale), categorized numerical rating scales with ordinal ranking of individual behaviors within three to seven "categories" (e.g., 0-2 points assigned for various behaviors within each of several behavior categories such as vocalization, movement, respiratory pattern, and posture), or visual analog scales (VAS 1 ). Verbal, numerical, categorized numerical, VAS, or a combination of two or more of these scales have been used to evaluate behavior in dogs in at least six studies of OHE or castration (Firth and Haldane 1999;Lascelles et al 1997;Lemke et al 2002;Slingsby and Waterman-Pearson 2000;Slingsby et al 2001); in 13 studies of orthopedic surgery (Brodbelt et al 1997;Budsberg et al 2002;Conzemius et al 1997;Day et al 1995;Grisneaux et al 1999;Hendrix et al 1996;Lascelles et al 1994;Mbugua et al 1989;Nolan and Reid 1993;Pibarot et al 1997;Sammarco et al 1996;Taylor and Houlton 1984;Vesal et al 1996); one study of auricular surgery (Buback et al 1996); seven studies of canine thoracotomies (Conzemius et al 1994;Pascoe and Dyson 1993;Popilskis et al 1991;Stobie et al 1995;Thompson and Johnson 1991;Vainio and Ojala 1994;Walsh et al 1999); and five studies of other soft tissue and/or orthopedic surgery patients ( Holton et al 1998a,b;Mathews et al 1996Mathews et al , 2001Reid and Nolan 1991). All of these scales are characterized by reliance on subjective evaluation of behaviors whose correlation with other behavioral or physiological indic...…”
Section: Potential Advantages For Investigatorsmentioning
confidence: 98%
“…This characteristic increases the likelihood of discordance between observers. For example, the following words may mean different things to different people and be impossible to define with enough precision to ensure good interobserver agreement: "uncomfortable" (Vesal et al 1996); "frequent" (Conzemius et al 1997); "calm" (Sammarco et al 1996); "hysterical" (Sammarco et al 1996); "responds to calm voice" (Conzemius et al 1997;Grisneaux et al 1999); "agitation" (Vesal et al 1996); "crying" (Pibarot et al 1997); "wary" (Firth and Haldane 1999); and "may not dream" (Mathews 1996).…”
Section: Potential Advantages For Investigatorsmentioning
confidence: 99%
“…Epidural opioids were found to be associated with nausea, vomiting, pruritus, urinary retention and respiratory depression in dogs 6,7 , and epidural administration of alpha 2 -agonists produced hypotension, bradycardia and sedation in children and dogs 5,8,9 . These adverse effects might not be appropriate in weakened animals or those with systemic disorders.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One consideration in evaluating these data, however, is that thoracotomy can induce ventilation–perfusion mismatch and atelectasis, and this combined with hypoventilation in dogs breathing room air would explain this degree of hypoxemia. Other studies in dogs have reported mild respiratory depression after various agonist opioids, including sufentanil (Polis et al, 2006), and epidural or intramuscular oxymorphone (Vesal et al, 1996). …”
Section: Discussionmentioning
confidence: 99%